Preparation method of ultrathin carrier copper foil with thickness not exceeding 1.5 microns, product and application of ultrathin carrier copper foil
By using cyanide as complexing agent and optimizing the electroplating solution formula in the preparation of ultra-thin copper foil, the thickness and stability problems are solved, and ultra-thin copper foil with efficient peeling and excellent apparent performance is achieved, suitable for a variety of electronics field.
Patent Information
- Application Number
- CN202411207127.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
AI Technical Summary
It is difficult to prepare stable and complete ultra-thin copper foils with a thickness of no more than 1.5 μm, and pinholes often appear on the surface of ultra-thin copper foils, which affect service life and conductivity.
Using cyanide as complexing agent to the metal alloy plating solution, the formulation of metal alloy plating solution and pre-plating solution and control the current density of the base layer deposition, a double-layer metal alloy peeling layer and base layer are prepared, and copper foil is deposited. To achieve stable peeling of ultra-thin copper foil.
The thickness of ultra-thin copper foil is achieved without exceeding 1.5μm, the peeling efficiency is higher than 99%, the apparent performance is excellent, and no pinholes are observed. It is suitable for electronic packaging, printed circuit boards and lithium-ion batteries.
Smart Images

Figure CN119121332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of electrolytic copper foil, and in particular relates to a preparation method of an ultra-thin carrier copper foil with a thickness not exceeding 1.5 μm, a product thereof and an application thereof. Background Art
[0002] At present, the fifth generation mobile communication technology (5th Generation Mobile Communication Technology, 5G) continues to deepen in the vertical field. As the first batch of mobile communication terminals that support 5G, such as smartphones, their printed circuit boards (PCBs) carrying chips and semiconductor components are gradually developing in the direction of miniaturization, high integration and high reliability. The precision, high density and high reliability of PCBs are related to the thickness of copper foil. The thicker the copper foil, the longer the etching time to remove the residual copper on the circuit, and the more serious the side etching phenomenon; when the circuit is finer, the side etching phenomenon is more obvious. If ultra-thin copper foil (thickness ≤ 12μm) is used, the etching time can be greatly reduced to ensure high-precision etching, so the requirements for electrolytic copper foil are also increased. Not only that, ultra-thin copper foil also has good electrical conductivity, thermal conductivity, flexibility and corrosion resistance, which makes ultra-thin copper foil have broad application prospects in electronic packaging, printed circuit boards, lithium-ion batteries and other fields.
[0003] As is known to all, as the thickness of ultra-thin copper foil is further reduced, the difficulty of stably and completely peeling it from the carrier will significantly increase. Therefore, the thickness of the currently disclosed ultra-thin copper foil can be as low as 2.5-3.5 μm, and there is no disclosure of the preparation method of ultra-thin copper foil below 2 μm.
[0004] Therefore, it is of great practical significance to develop a method for preparing ultra-thin copper foil with a thickness not exceeding 1.5 μm. Summary of the invention
[0005] In view of the above problems, the present invention discloses a method for preparing an ultra-thin carrier copper foil. The prepared ultra-thin copper foil has a thickness of no more than 1.5 μm and can be stably and completely peeled off from the carrier with a peeling efficiency higher than 99%. The ultra-thin copper foil has good surface performance and no pinholes are observed.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] A method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm, comprising:
[0008] S1: pre-treating the surface of the metal support;
[0009] S2: preparing a metal alloy electroplating solution to deposit a double-layer metal alloy peeling layer on the surface of the pretreated metal support;
[0010] The metal alloy electroplating solution includes two or more of zinc salt, chromium salt, cobalt salt, nickel salt and molybdenum salt;
[0011] The metal alloy electroplating solution also includes a complexing agent, and the complexing agent is selected from cyanide;
[0012] S3: Prepare a pre-plating solution, and deposit a base layer on the surface of the metal carrier on which the metal alloy peeling layer is deposited. The deposition current density is 2 to 4 A / dm 2 ;
[0013] The pre-plating solution comprises: 5-30 g / L cuprous cyanide, 10-40 g / L sodium cyanide, 10-30 g / L sodium carbonate, and 1-5 g / L sodium hydroxide;
[0014] S4: preparing a copper plating solution, and depositing a copper layer on the surface of the metal carrier on which the base layer is deposited, to obtain an ultra-thin carrier copper foil.
[0015] In the preparation method disclosed in the present invention, cyanide is added to the metal alloy electroplating solution as a complexing agent, the pre-plating solution used is a cyanide-based plating solution, and the ultra-thin copper foil prepared has a thickness of no more than 1.5 μm by optimizing the formula of the metal alloy electroplating solution and the formula of the pre-plating solution and accurately controlling the current density of the substrate deposition. The foil can be stably and completely peeled off from the carrier, the peeling efficiency is higher than 99%, and the ultra-thin copper foil has good surface performance and no pinholes are observed.
[0016] Experiments have found that if no chelating agent is added to the metal alloy electroplating solution, the prepared ultra-thin copper foil will fall off directly from the carrier, and there will be a large number of pinholes on the surface of the copper foil. The appearance of pinholes will not only affect the appearance quality and reduce the service life, but may also cause circuit short circuits and reduce conductivity in downstream applications. If the added chelating agent is other types of chelating agents commonly found in electroplating solutions, such as potassium pyrophosphate, the prepared ultra-thin copper foil film will have a large number of pinholes and the stripping efficiency will decrease.
[0017] The test also found that if the pre-plating solution is replaced by a pyrophosphate plating solution, the normal peel strength of the prepared ultra-thin copper foil is significantly reduced, and there are a large number of pinholes on the surface, and the peeling efficiency is also significantly reduced. If the pre-plating solution is replaced by a pyrophosphate plating solution, and the complexing agent in the metal alloy electroplating solution is replaced by potassium pyrophosphate, although the peeling strength and peeling efficiency are improved, and the number of pinholes is also reduced, it is still significantly inferior to the ultra-thin copper foil prepared by the system of the present invention.
[0018] The experiment found that even if the metal alloy electroplating solution formula and pre-plating solution formula are optimized, the current density of the substrate deposition needs to be further controlled. If the current density is too low or too high, the performance of the prepared ultra-thin copper foil will be unqualified.
[0019] In step S1:
[0020] The metal carrier is selected from steel plate;
[0021] The pretreatment includes polishing and pickling.
[0022] In step S2:
[0023] In the metal alloy electroplating solution, the total concentration of the alloy salt is 2-20 g / L, the concentration of the complexing agent is 10-30 g / L, and the pH value of the electroplating solution is 7-12.
[0024] The cyanide is selected from sodium cyanide and / or potassium cyanide.
[0025] The current density of the deposited metal alloy stripping layer is 1 to 15A / dm 2 , deposition time is 10 to 120 s;
[0026] Preferably, the current density of the deposited metal alloy stripping layer is 1 to 5 A / dm 2 , the deposition time is 10 to 60 seconds.
[0027] Preferred:
[0028] In step S2, the metal alloy stripping layer is selected from a zinc-molybdenum alloy layer, a nickel-molybdenum alloy layer, a zinc-cobalt alloy layer or a nickel-cobalt alloy layer.
[0029] The experiment found that the comprehensive performance of the ultra-thin copper foil prepared by using a double-layer metal alloy peeling layer is significantly better than that of the ultra-thin copper foil prepared by using only a single-layer metal alloy peeling layer.
[0030] More preferably, the two metal alloy peeling layers have different compositions.
[0031] In step S3:
[0032] The pre-plating solution comprises: 10-20 g / L cuprous cyanide, 20-30 g / L sodium cyanide, 10-20 g / L sodium carbonate, and 1-5 g / L sodium hydroxide;
[0033] The deposition time of the base layer is 5 to 25 seconds.
[0034] In step S4, the composition of the copper plating solution includes: 30-100 g / L copper ions, 60-120 g / L sulfuric acid, 20-100 mg / L activated carbon, and Cl -10~50mg / L, hydroxyethyl cellulose 10~50mg / L, collagen 1~10mg / L; the plating solution temperature is 25~55℃, and the flow rate is 0.1~1.0m 3 / h.
[0035] Preferably, the current density of the deposition in step S4 is 5 to 15 A / dm 2 , time is 20 to 150s.
[0036] The invention also discloses an ultra-thin carrier copper foil prepared according to the method, comprising a carrier, an isolation layer and an ultra-thin copper foil, wherein the thickness of the ultra-thin copper foil is ≤1.5 μm.
[0037] The invention also discloses the application of the ultra-thin carrier copper foil in the fields of electronic packaging, printed circuit boards and lithium ion batteries.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The invention discloses a method for preparing an ultra-thin carrier copper foil, which has simple process, low cost and high production efficiency.
[0040] The ultra-thin copper foil in the ultra-thin carrier copper foil prepared by the present invention has a thickness of ≤1.5 μm, a uniform thickness, a flat and smooth surface, no pinholes observed, and no obvious defects; under normal conditions, it has a suitable peeling strength with the metal carrier, is not easy to fall off, and can be stably and completely peeled off from the carrier, with a peeling efficiency higher than 99%.
[0041] The ultra-thin carrier copper foil prepared by the present invention is expected to be widely used in the fields of electronic packaging, such as chip packaging, integrated circuit packaging, etc., printed circuit boards and lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a microscope photo of the ultra-thin carrier copper foil slice prepared in this embodiment, with a magnification of 50 times. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto.
[0044] Unless otherwise specified, the raw materials in the examples and comparative examples of the present invention were purchased through commercial channels.
[0045] Example 1
[0046] (1) Polishing of steel plate
[0047] A 316L stainless steel plate with a thickness of 1 mm and a size of 10 cm×13 cm was selected, polished, and the surface oxide film was washed away with an 8 wt % sulfuric acid aqueous solution.
[0048] (2) Preparation of metal release layer
[0049] The composite metal alloy peeling layer is deposited on the surface of the polished steel plate. The zinc-molybdenum alloy layer is first deposited at a current density of 2A / dm 2 , the deposition time is 30s; then the nickel-molybdenum alloy layer is deposited, and the current density is 1A / dm 2 , the deposition time is 30s.
[0050] The specific composition of the plating solution is as follows:
[0051] Zinc-molybdenum alloy electroplating solution: zinc sulfate heptahydrate 3g / L, ammonium molybdate tetrahydrate 1g / L, sodium cyanide 15g / L, plating temperature 30℃.
[0052] Nickel-molybdenum alloy electroplating solution: nickel sulfate hexahydrate 10g / L, ammonium molybdate tetrahydrate 5g / L, sodium cyanide 50g / L, plating temperature 30℃.
[0053] (3) Preparation of base layer
[0054] The base layer is continuously deposited on the surface of the steel plate on which the composite metal alloy peeling layer is deposited, and the current density is 3A / dm 2 , the deposition time is 20s.
[0055] The specific composition of the plating solution is as follows:
[0056] The concentration of cuprous cyanide is 15 g / L, the concentration of sodium cyanide is 23 g / L, the concentration of sodium carbonate is 15 g / L, the concentration of sodium hydroxide is 3 g / L, and the temperature of the electroplating solution is 25°C.
[0057] (4) Preparation of ultra-thin copper foil
[0058] Ultra-thin copper foil is continuously deposited on the surface of the substrate with a current density of 10A / dm 2 , the deposition time is 120s, and an ultra-thin carrier copper foil is prepared.
[0059] The specific composition of the plating solution is as follows:
[0060] The copper ion concentration is 50g / L, the sulfuric acid concentration is 70g / L, the activated carbon concentration is 30mg / L, and the Cl - The concentration is 30 mg / L, the concentration of hydroxyethyl cellulose is 30 mg / L, the concentration of collagen is 5 mg / L, the plating solution temperature is 45°C, and the flow rate is 1m 3 / h.
[0061] Figure 1 This is a microscope photograph of the ultra-thin carrier copper foil prepared in this embodiment. From the photograph, it can be seen that the thickness of the ultra-thin carrier copper foil is 1.47 μm.
[0062] Example 2
[0063] The preparation process is basically the same as that in Example 1, except that in step (2):
[0064] The zinc-cobalt alloy layer was deposited instead of the zinc-molybdenum alloy layer, and the deposition current density was 1A / dm 2 , the deposition time is 30s, and the composition of the plating solution used is:
[0065] Zinc sulfate heptahydrate 5g / L, cobalt sulfate heptahydrate 2g / L, sodium cyanide 25g / L, plating solution temperature 30℃.
[0066] Example 3
[0067] The preparation process is basically the same as that in Example 1, except that in step (2):
[0068] The first deposition of the zinc-molybdenum alloy layer is replaced by the first deposition of the nickel-cobalt alloy layer, and the deposition current density is 1A / dm 2 , the deposition time is 30s, and the composition of the plating solution used is:
[0069] Nickel sulfate hexahydrate 2g / L, cobalt sulfate heptahydrate 1g / L, sodium cyanide 10g / L, plating solution temperature 30℃.
[0070] Example 4
[0071] The preparation process is basically the same as that in Example 1, except that in step (2):
[0072] The redeposited nickel-molybdenum alloy layer is replaced by a redeposited nickel-cobalt alloy layer, and the deposition current density is 1A / dm 2 , the deposition time is 30s, and the composition of the plating solution used is:
[0073] Nickel sulfate hexahydrate 2g / L, cobalt sulfate heptahydrate 1g / L, sodium cyanide 10g / L, plating solution temperature 30℃.
[0074] Example 5
[0075] The preparation process is basically the same as that in Example 1, except that in step (3):
[0076] When depositing the base layer, the current density was changed to 2A / dm 2 .
[0077] Example 6
[0078] The preparation process is basically the same as that in Example 1, except that in step (3):
[0079] When depositing the base layer, the current density was changed to 4A / dm 2 .
[0080] Comparative Example 1
[0081] The preparation process is basically the same as that in Example 1, except that in step (3):
[0082] When depositing the base layer, the current density was changed to 1A / dm 2 .
[0083] Comparative Example 2
[0084] The preparation process is basically the same as that in Example 1, except that in step (3):
[0085] When depositing the base layer, the current density was changed to 5A / dm 2 .
[0086] Comparative Example 3
[0087] The preparation process is basically the same as that in Example 1, except that in step (3):
[0088] The plating solution used to deposit the base layer is different, and the specific composition is:
[0089] The potassium pyrophosphate concentration is 280 g / L, the copper pyrophosphate concentration is 80 g / L, and the plating solution temperature is 45°C.
[0090] Comparative Example 4
[0091] The preparation process is basically the same as that in Comparative Example 3, except that in step (3):
[0092] When depositing the base layer, the current density was changed to 5A / dm 2 .
[0093] Comparative Example 5
[0094] The preparation process is basically the same as that in Example 1, except that step (3) is not performed, that is, the ultra-thin copper foil is directly deposited on the surface of the steel plate on which the composite metal alloy peeling layer is deposited.
[0095] Comparative Example 6
[0096] The preparation process is basically the same as that in Example 1, except that in step (2):
[0097] Only a zinc-molybdenum alloy peeling layer is deposited on the surface of the polished steel plate, and the composition of the zinc-molybdenum alloy electroplating solution and the deposition current density and time remain unchanged.
[0098] Comparative Example 7
[0099] The preparation process is basically the same as that in Example 1, except that in step (2):
[0100] No sodium cyanide is added to the prepared zinc-molybdenum alloy electroplating solution and nickel-molybdenum alloy electroplating solution.
[0101] Comparative Example 8
[0102] The preparation process is basically the same as that in Example 1, except that in step (2):
[0103] In the prepared zinc-molybdenum alloy electroplating solution and nickel-molybdenum alloy electroplating solution, sodium cyanide is replaced with an equal mass of potassium pyrophosphate.
[0104] Comparative Example 9
[0105] The preparation process is basically the same as that in Comparative Example 3, except that in step (2):
[0106] In the prepared zinc-cobalt alloy electroplating solution and nickel-molybdenum alloy electroplating solution, sodium cyanide is replaced with an equal mass of potassium pyrophosphate.
[0107] Comparative Example 10
[0108] The preparation process is basically the same as that in Example 1, except that step (2) is not performed, that is, the base layer is directly deposited on the surface of the polished steel plate.
[0109] Performance Testing
[0110] In order to more clearly show the effects of the preparation formulas and electroplating processes of different embodiments and comparative examples on the properties of the ultra-thin copper foil, the following tests were performed on the carrier copper foils prepared in embodiments 1 to 6 and comparative examples 1 to 10 respectively:
[0111] Peel strength test: Fix the carrier with ultra-thin copper foil on a universal mechanical testing machine, apply tension at a speed of 50mm / min, the peel width is 50mm, and the peel length is 30mm. During the test, observe the changes in peel distance and peel data.
[0112] Observe the pinhole condition: stick the ultra-thin copper foil on the adhesive film, illuminate it with a parallel light source, and record the number of pinholes.
[0113] Thickness analysis: The ultra-thin copper foil is combined with the substrate by hot pressing, and small samples are cut for slicing, and then placed under a metallographic microscope for observation at a magnification of 50 times.
[0114] Stripping efficiency test: Hundreds of experiments were conducted to statistically analyze the complete stripping efficiency of ultra-thin copper foil.
[0115] Table 1
[0116] serial number Copper foil thickness / μm Normal peeling Peel strength (N / mm) Number of pinholes Stripping efficiency / % Example 1 1.47 Completely peeled off 0.045 No pinholes >99 Example 2 1.50 Completely peeled off 0.061 No pinholes >99 Example 3 1.47 Completely peeled off 0.033 No pinholes >99 Example 4 1.45 Completely peeled off 0.046 No pinholes >99 Example 5 1.47 Completely peeled off 0.040 No pinholes >99 Example 6 1.46 Completely peeled off 0.037 No pinholes >99 Comparative Example 1 1.45 Completely peeled off 0.03 20~25 >99 Comparative Example 2 / Shedding / No pinholes / Comparative Example 3 1.46 Completely peeled off 0.002 >50 >80 Comparative Example 4 / Shedding / >50 / Comparative Example 5 / Unable to peel off / / / Comparative Example 6 1.44 Completely peeled off 0.005 10~12 / Comparative Example 7 / Shedding / >50 / Comparative Example 8 1.50 Completely peeled off 0.03 20~25 >95 Comparative Example 9 1.47 Completely peeled off 0.01 20~25 >95 Comparative Example 10 / Shedding / >50 /
[0117] Observing the data in Table 1, Examples 1 to 6 adopt the preparation process and raw material system disclosed in the present invention, and the thickness of the ultra-thin copper foil prepared does not exceed 1.5 μm, and normal peeling can be achieved with moderate peeling strength and high peeling efficiency; the surface is flat and smooth, no pinholes are observed, and there are no obvious defects.
[0118] By comparing Example 1 with Comparative Examples 5 and 10, it can be seen that both the peeling layer and the base layer are indispensable in the preparation process.
[0119] By comparing Examples 1, 5, and 6 with Comparative Examples 1 and 2, it can be seen that while optimizing the metal alloy electroplating solution formula and the pre-plating solution formula, it is also necessary to accurately control the current density of the substrate layer deposition. If the current density is too low or too high, the performance of the prepared ultra-thin copper foil will be unqualified.
[0120] By comparing Example 1 with Comparative Examples 3, 4, and 7 to 9, it can be seen that only by adopting the metal alloy electroplating solution formula and the pre-plating solution formula that are simultaneously optimized disclosed in the present invention can an ultra-thin copper foil with excellent performance be prepared, while if the metal alloy electroplating solution formula and the pre-plating solution formula are adjusted separately, or if both are replaced at the same time, a technical effect equivalent to that of the present invention cannot be obtained.
[0121] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm, characterized in that: include: S1: pre-treating the surface of the metal support; S2: preparing a metal alloy electroplating solution to deposit a double-layer metal alloy peeling layer on the surface of the pretreated metal support; The metal alloy electroplating solution includes two or more of zinc salt, chromium salt, cobalt salt, nickel salt and molybdenum salt; The metal alloy electroplating solution also includes a complexing agent, and the complexing agent is selected from cyanide; S3: Prepare a pre-plating solution, and deposit a base layer on the surface of the metal carrier on which the metal alloy peeling layer is deposited. The deposition current density is 2 to 4 A / dm 2 ; The pre-plating solution comprises: 5-30 g / L cuprous cyanide, 10-40 g / L sodium cyanide, 10-30 g / L sodium carbonate, and 1-5 g / L sodium hydroxide; S4: preparing a copper plating solution, and depositing a copper layer on the surface of the metal carrier on which the base layer is deposited, to obtain an ultra-thin carrier copper foil.
2. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S1: The metal carrier is selected from a steel plate; The pretreatment includes polishing and pickling.
3. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S2: In the metal alloy electroplating solution, the total concentration of the alloy salt is 2 to 20 g / L, the concentration of the complexing agent is 10 to 30 g / L, and the pH value of the electroplating solution is 7 to 12; The cyanide is selected from sodium cyanide and / or potassium cyanide; The current density of the deposited metal alloy stripping layer is 1 to 15A / dm 2 , the deposition time is 10 to 120 seconds.
4. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S2, the metal alloy stripping layer is selected from a zinc-molybdenum alloy layer, a nickel-molybdenum alloy layer, a zinc-cobalt alloy layer or a nickel-cobalt alloy layer.
5. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S3: The pre-plating solution comprises: 10-20 g / L cuprous cyanide, 20-30 g / L sodium cyanide, 10-20 g / L sodium carbonate, and 1-5 g / L sodium hydroxide; The deposition time is 5 to 25 seconds.
6. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S4, the composition of the copper plating solution includes: 30-100 g / L copper ions, 60-120 g / L sulfuric acid, 20-100 mg / L activated carbon, and Cl - 10~50mg / L, hydroxyethyl cellulose 10~50mg / L, collagen 1~10mg / L; the plating solution temperature is 25~55℃, and the flow rate is 0.1~1.0m 3 / h.
7. The method for preparing an ultra-thin carrier copper foil having a thickness not exceeding 1.5 μm according to claim 1, characterized in that: In step S4, the deposition current density is 5 to 15 A / dm 2 , time is 20 to 150s.
8. An ultra-thin carrier copper foil prepared according to the method according to any one of claims 1 to 7, characterized in that: The invention comprises a carrier, an isolation layer and an ultra-thin copper foil, wherein the thickness of the ultra-thin copper foil is less than or equal to 1.5 μm.
9. Use of the ultra-thin carrier copper foil according to claim 8 in the fields of electronic packaging, printed circuit boards and lithium-ion batteries.
